2021
DOI: 10.1021/acs.nanolett.1c00632
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Triplet-Mediated Multicolor Lasing from Nondoped Organic TADF Microcrystals

Abstract: Thermally activated delayed fluorescent (TADF) emitters have received great attention in organic light-emitting diodes and laser diodes because of high exciton utilization efficiency and low optical loss caused by triplets. However, the direct observation of lasing emission from nondoped TADF microcrystals has yet to be reported. Here, we demonstrated a three-color (green, yellow, and red) microlaser from three nondoped TADF microcrystals with well-controlled geometries. The temperature-dependent dynamic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 41 publications
0
36
0
Order By: Relevance
“…In addition, two microcrystals exhibit as active optical waveguides with brighter PL edge and weaker PL from the bodies (Figure 1b and Figure S3, Supporting Information), which shows that they might potentially serve as active media for both PL emission and optical resonators. [ 34 ] It should point out that the state‐of‐the‐art PCF materials often require a pressure of GPa level to achieve luminescence and/or intrinsic color regulation, [ 29,30 ] which caused the destruction of crystal morphology and restricted their practical applications. We demonstrated that the fluorescence switching of TPIZ microcrystals can be achieved under only 1.0 MPa, while the retentive crystal morphology provided the possibility of TPIZ as a candidate for force‐induced laser output.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, two microcrystals exhibit as active optical waveguides with brighter PL edge and weaker PL from the bodies (Figure 1b and Figure S3, Supporting Information), which shows that they might potentially serve as active media for both PL emission and optical resonators. [ 34 ] It should point out that the state‐of‐the‐art PCF materials often require a pressure of GPa level to achieve luminescence and/or intrinsic color regulation, [ 29,30 ] which caused the destruction of crystal morphology and restricted their practical applications. We demonstrated that the fluorescence switching of TPIZ microcrystals can be achieved under only 1.0 MPa, while the retentive crystal morphology provided the possibility of TPIZ as a candidate for force‐induced laser output.…”
Section: Resultsmentioning
confidence: 99%
“…Further progress has been made in recent years. [43][44][45][46][47][48][49][50][51][52] Since the first attempt to use TADF materials in OLEDs, [53,54] various TADF materials have been designed and synthesized. [55][56][57] However, only some of these materials have been reported to exhibit laser activity.…”
Section: Introductionmentioning
confidence: 99%
“…[55][56][57] However, only some of these materials have been reported to exhibit laser activity. [43][44][45][46][47][48][49][50][51][52] The relationship between the molecular structures of TADF materials and their laser properties remains unclear. Recent progress in TADF gain materials is reviewed in this paper to illustrate the recent advances in TADF gain materials, raise awareness of this new field and extract the fundamental design principles and strategies of TADF gain materials.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the T 2 state involved in the TADF mechanism has begun to draw increased attention. The incipient criterion of the T 2 -mediated TADF channel in a few studies only concentrates on both the sufficiently small splitting energy |ΔE S1-T2 | (|ΔE S1-T2 | < |ΔE S1-T1 |) and large SOC value between S 1 and T 2 , [13,14] without considering the T 2 − T 1 gap. Afterward, some studies have shown that the T 2 -mediated T 1 → T 2 → S 1 TADF channel (Scheme 1c) is formed by populating T 2 excitons from T 1 through Boltzmann statistics, spin−vibronic coupling, and reverse internal conversion (RIC) on the basis of a narrow T 2 − T 1 gap.…”
Section: Introductionmentioning
confidence: 99%